Health insurance non-enrollment among women in Sierra Leone: A cross-sectional analysis of the 2019 Demographic and Health Survey. - Augustus Osborne; Mainprice Akuoko Essuman; Peter Bai James; Camilla Bangura; Richard Gyan Aboagye; Comfort Z Olorunsaiye; Abdul-Aziz Seidu; Bright Opoku Ahinkorah (PLoS ONE)
Background Health insurance enrollment is a vital component of universal health coverage and access to essential healthcare services. However, in Sierra Leone, enrollment remains persistently low, posing a major public health challenge. Women of reproductive age (15-49 years) represent a critical population for health insurance enrollment due to their unique healthcare needs, particularly related to reproductive health, pregnancy, and childcare. Despite their importance, women face notable barriers to health insurance enrollment, including financial constraints, gender inequalities, and sociocultural challenges. This study examines the factors associated with health insurance non-enrollment among women aged 15-49 in Sierra Leone. Methods We analysed data from a weighted sample of 15,574 women aged 15-49 years from the 2019 Sierra Leone Demographic and Health Survey. Percentages were used to present the proportion of health insurance non-enrollment among the women. Multivariable binary logistic regression analysis was used to examine the factors associated with health insurance non-enrollment among the women. Results The proportion of health insurance non-enrollment among the women was 96.02%. Women with higher education were less likely to be uninsured (adjusted odds ratio [aOR]: 0.35, 95% CI: 0.18-0.64) compared to those with no education. Being employed also reduced the odds of being uninsured (aOR: 0.47, 95% CI: 0.36-0.62) compared to women who were employed. Listening to the radio less than once a week was associated with lower odds of being uninsured (aOR: 0.71, 95% CI: 0.53-0.97) compared to women who did not listen to the radio at all. On the other hand, women who reported distance to a health facility as a big problem were more likely to be uninsured (aOR: 2.21, 95% CI: 1.03-4.75) compared to those who did not consider it a problem. Regionally, women living in the Northwestern (aOR: 0.07, 95% CI: 0.03-0.14) and Northern (aOR: 0.28, 95% CI: 0.12-0.66) regions were less likely to be uninsured compared to those residing in the Eastern region. Conclusions Health insurance non-enrollment was high among women in Sierra Leone. Education, employment, and exposure to listening to the radio were associated with increased health insurance enrollment, highlighting the need to address socioeconomic barriers and leveraging mass media campaigns to educate women on the importance of getting covered by health insurance. Geographic and regional disparities in health insurance enrollment underscore the importance of improving healthcare accessibility and implementing targeted, community-based interventions to promote health insurance uptake. Also, subsiding health insurance subscription fee could increase its enrollment, especially among women from low socioeconomic households.